Accounting : - Horngren, Charles T. (Prentice-Hall, 1996)
This new revision incorporates feedback from student and professor focus groups as well as extensive reviewer surveys. The dramatic new design focuses on visually reinforcing and teaching the text topics. All major topics are taught in a business, decision-making context. Accounting 3/E pays very careful attention to making accounting information interesting and relevant to students